Competitive profiling of ligandable cysteines in Staphylococcus aureus with an organogold compound. Issue 36 (14th April 2022) - Schmidt, Claudia; Zollo, Michael; Bonsignore, Riccardo; Casini, Angela; Hacker, Stephan M.
Abstract : With the idea of exploiting metal templated C–S bond forming reactions to achieve modification of cysteines in bacterial proteins, a cyclometalated Au(iii ) compound was explored in a competitive chemoproteomic approach in S. aureus cell extracts. Abstract : With the idea of exploiting metal templated C–S bond forming reactions to achieve modification of cysteines in bacterial proteins, a cyclometalated Au(iii ) compound was explored in a competitive chemoproteomic approach in S. aureus cell extracts. More than 100 ligandable cysteines were identified, of which more than 50% were not engaged by organic α-chloroacetamides in a previous study, indicating that organometallic compounds expand the ligandable space in bacteria. A selected interaction was validated using an enzyme activity assay, and intact protein mass spectrometry showed cysteine arylation of an unprecedented target. The obtained results demonstrate that this family of organogold compounds has potential for therapeutic protein targeting via selective, covalent modification of cysteine residues in bacteria.